Skills of Regional Head Leadership on Community Satisfaction in the Field of Health and Education in the Islands District in North Sulawesi - Toni Supit; David. P.E. Saerang; Bernhard Tewal; Victor .P.K. Lengkong; Agus T. Poputra (Journal of The Community Development in Asia, 2019)
The purpose of this study was to analyze the influence of the Regional Head Leadership Skills variable (X), on Community Satisfaction (Y3) with the intervening variable is Professionalism of State Civil Service (Y1), and Service Quality (Y2) in health and education in island districts in North Sulawesi. The results of the study show that: (1) the skills of regional head leadership have a positive and significant influence on the professionalism of the state civil apparatus that provides public services in the health and education fields; (2) the leadership skills of regional heads have a positive and significant influence on the quality of public services in the health and education fields, both directly and through the professionalism of the state civil apparatus; (3) the skills of regional head leadership provide a positive and significant influence on community satisfaction regarding health and education services, both directly and through the professionalism of the state civil apparatus and the quality of public services; (4) the professionalism of the state civil apparatus has a positive and significant influence on the quality of services; (5) the professionalism of the state civil apparatus has a positive and significant influence on community satisfaction, both directly and through the quality of services; and (6) the quality of services in the health and education fields has a positive and significant effect on community satisfaction. Keywords: Regional Leadership Skills, Community Satisfaction, Professionalism of State Civil Apparatus, Service Quality, Community Satisfaction, Islands Regency, North Sulawesi.